Analysis Of Liquidity Ratio, Solvency Ratio, And Profitability Ratio To Bond Ratings In Food And Beverages Companies Listed On The Indonesia Stock - Suriyanti Suriyanti; Sidik Priadana; Pudji Astuty (Jurnal Pendidikan Nusantara, 2022)
This study aims to analyze the effect of liquidity on bond ratings for food and beverages companies listed on the Indonesia Stock Exchange for the 2016- 2020 period, to analyze the impact of solvency on bond ratings for food and beverages companies listed on the Indonesia Stock Exchange for the 2016-2020 period, to analyze the effect of profitability on bond ratings for food and beverages companies listed on the Indonesia Stock Exchange for the 2016-2020 period, and to analyze the impact of liquidity, solvency, and profitability simultaneously on the financial sector listed on the Indonesia Stock Exchange for the 2016-2020 period. This research is a quantitative study with secondary data in the form of company financial statements for 2016-2020 obtained from the Indonesia Stock Exchange or the website of each company and bond rating data published by bond rating agencies, namely PT. PEFINDO for five consecutive years. The sampling technique used the purposive sampling method. The t-test or partial test results show that solvency significantly affects bond ratings in food and beverage companies listed on the Indonesia Stock Exchange for the 2016 - 2020 period. The F test results show that the variables CR, DER, and ROA jointly positively affect Bond ratings for food and beverages companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Then the coefficient of determination analysis (R2) results simultaneously explain that Liquidity, Solvency, and Profitability influence the Bond Rating variable for food and beverages companies listed on the Indonesian Stock Exchange. Indonesia Stock Exchange Period 2016 2020